Engineering properties of residual soils - Anuar, Ibrahim. (Universiti Malaysia Sarawak, UNIMAS, 2010)
The residual soils are earthen formed of weathering process on rock and remained at the place where it was formed. Many studies were made to determine the engineering properties of resi dual soil in Malaysia but until now in Sarawak not much data can be found for the engineering properties of residual soil. Thus, the main objectives are to determine index properties and to investigate on engineering properties of residual soil in Kota Sam arahan, Sarawak. Varies of physical and engineering properties tests have been conducted for three samples which taken from three different locations. The three locations are for the Institut Latihan Perindustrian Kota Samarahan, Vista Aman housing area, a nd Samarahan Expressway near the UiTM Samarahan roundabout represented with sample A, B and C respectively. Experimental results show that the natural moisture content is in range of 22 to 32.3%. The specific gravity (G s ) of the residual soil samples teste d ranges from 2.65 to 2.67. The liquid limit of the soil varies from 43 to 58%. Sample A has the lowest value of liquid limit as compared to sample B and sample C. The Optimum Moisture Content (OMC) and maximum dry density for residual soil are varying fro m 20.0 to 26.5% and 1.47 to 1.60 Mg/m 3 , respectively. The value of compression index (C c ) and coefficient of consolidation (C v ) for the residual soil vary from 0.133 to 0.232 and 2.314 to 6.941 m 2 /year respectively. Then, the shear strength parameters, val ue of angle of internal friction (υ) vary from 10.94° to 17.14° and the cohesion (c) vary from 8.83 to 18.64 kN/m 2 . Next, the initial void ratio (e) for the residual soil tested is in a range of 0.786 to 1.0199.